Analisis Rangkaian Listrik Seri dan Paralel pada Mata Kuliah Praktikum IPA - Nirmala Eisya, Ratu; Ardea Pramesti; Reevalina Febiana; Nurul Hasanah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Practical activities in science as well as experiments are essential as a learning activity aimed at understanding the improvement of psychomotor learning outcomes and science process skills through simple practical methods. Science learning needs to be packaged attractively so that students are enthusiastic about learning. This research examines how static electricity, dynamic electricity, and series and parallel electrical circuits work. The research method used is descriptive qualitative with a science study approach from various relevant articles. The data source used is secondary information, obtained from relevant scientific journal articles published between 2019 and 2025. The data analysis process is conducted qualitatively, by gathering, examining, and sorting references that align with the focus of the study, and then systematically organizing them to produce deep and comprehensive conclusions. The study results indicate that the introduction of this new practical test improves the clarity of information and provides new knowledge and insights. Evaluations also demonstrate that the presence of this practical exercise makes learning more efficient for students. This finding emphasizes that competence in science studies, which underpins practical work and trials, is one of the efficient learning methods.